Peran Produser Dalam Mengoptimalkan Produktivitas Kerabat Kerja Pada Produksi Film Fiksi Penantian Kembali Bersamamu - Rahmad Fajar; FX. Yatno Karyadi (CV. ITTC INDONESIA, 2026)
Film production is a collaborative creative process involving various crew members with different responsibilities and competencies. Therefore, the producer plays a crucial role in managing human resources to optimize work productivity throughout the production process. This creative thesis aims to describe the producer’s role in optimizing crew productivity during the production of the fiction film Penantian Kembali Bersamamu. The film portrays the emotional relationship between an elderly father and his daughter, highlighting themes of loss, longing, and family reconciliation. The creative method applied in this study consists of four stages: preparation, planning, production, and presentation. The analysis of the producer’s role refers to Mathis and Jackson’s productivity theory, which includes appropriate job placement, work coordination, achievement of production targets within the scheduled time, and budget efficiency. The findings reveal that the producer optimized crew productivity through script breakdown analysis, competency-based crew selection and placement, structured coordination using pre-production meetings, script reading, technical recce, daily briefings, and production evaluations. Furthermore, effective scheduling strategies and budget management enabled the production to complete five to six scenes per day, exceeding the initial target of four to five scenes, while maintaining production quality. The total production cost was approximately IDR 15.8 million from the planned budget of IDR 20 million. These findings demonstrate that effective managerial decisions by the producer significantly contribute to improving crew productivity and achieving both artistic and production objectives.